Path dependence on the decisions implemented by the ecuadorian banking business groups (1970-2000) (2017)
This article had as an objective to analyze by using the Theory of Path Dependence the decisions that were taken by the banking groups during the period 1970-2000. In order to accomplish this goal, this current paper applied the methodology of Quivy and Campenhoudt. The results showed that the dependence on the path remained with positive returns despite the exogenous factors that occurred during phase I. It was concluded that the results were negative in the lock in phase. © 2017.